Emerging technologies and opportunities in the next millenium : OLEOCHEMICALS proceedings 1999 PORIM International Palm Oil Congress, 1-6 February 1999, Kuala Lumpur Istana Hotel, Malaysia - PORIM International Palm Oil Congress (1999 : Kuala Lumpur, Malaysia); PORIM (KL : PORIM, 1999)
50